2012
DOI: 10.1155/2012/952645
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma in the Elderly and SIADH: Case Report and Review of the Literature

Abstract: Objective. To report the rare case of a thymic neuroblastoma, in an elderly woman with SIADH at presentation. Methods. Clinical and biochemical data of the patient are presented and the pertinent literature is reviewed. Results. a 79-year-old woman was admitted into our department with worsening asthenia, severe hyponatremia (114.8 mEq/L), low plasma osmolarity (253 mEq/L), and inappropriate urinary sodium concentration (151 mEq/L). CT scan showed an a large solid inhomogeneous mass in the anterior mediastinum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The exceedingly rare neuroblastomas and ganglioneuroblastomas of the thymic region are unusual, since they occur in elderly patients. 86, 87 It is unknown, whether they are genetically distinct from their childhood counterparts.…”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%
“…The exceedingly rare neuroblastomas and ganglioneuroblastomas of the thymic region are unusual, since they occur in elderly patients. 86, 87 It is unknown, whether they are genetically distinct from their childhood counterparts.…”
Section: Novelties In the New Who Classification Of Mediastinal Tumorsmentioning
confidence: 99%
“…Neuroblastoma (NB), a common solid tumor in childhood, is infrequent in patients over 10 years of age. Adolescent and young adult (AYA) NBs are usually included as older patients, whereas NB in middle-aged and elderly adults is often ignored in these studies [1] , [2] , [3] , [4] , [5] . Several studies have demonstrated that tumors of older NB patients present a worse prognosis than their childhood NB counterparts, despite the presence of very few unfavorable biologic markers [3] , [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…12 Literature review showed many primary site neuroblastomas spreading to others parts of the body, but none of these patients below 3 years of age presented with large cheek mass. 13 Neuroblastomas have a very broad spectrum of clinical behavior which ranges from spontaneous regression to maturation to a benign ganglioneuroma, or aggressive disease with metastasis leading to death.…”
Section: Discussionmentioning
confidence: 99%